Role of Prostaglandin in Induction of Labor in Patients with Poor Bishop Score - Fazal, Safia; Darwaish, Ayesha; Noor, Sumia; Khan, Sundas (Indus Journal of Bioscience Research, 2025)
Background: Low Bishop score is a sign of an adverse cervix and is significantly linked to labor induction failure. Prostaglandins have been increasingly employed to address this dilemma as they induce cervical ripening and uterine contractility to enhance successful vaginal discharge. Creation of local evidence is necessary in order to authenticate their application in varied clinical scenarios. Objective: To evaluate the efficacy of prostaglandin for induction of labor in women presenting with a poor Bishop score. Study Design: Quasi-experimental study. Duration and Place of Study: The study was carried out from July 2024 to December 2024 at the Department of Obstetrics and Gynecology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 118 women aged 18 to 40 years with singleton pregnancies beyond 37 weeks and an unfavorable Bishop score of five or less were included. Exclusion criteria were previous cesarean section, contraindications to prostaglandin use, abnormal fetal presentation, uterine pathology, or non-reassuring fetal status. Labor was induced with intravaginal prostaglandin E2 gel, administered up to three times within 24 hours. Efficacy was defined as achievement of vaginal delivery within 24 hours after induction. Results: The mean age of participants was 28 years and the mean gestational age was 39 weeks. Among 118 cases, successful vaginal delivery occurred in 100 women (84.7%), while 18 women (15.3%) failed to respond to induction. No significant association was found between efficacy and demographic factors. Conclusion: Prostaglandin is an effective agent for labor induction in women with poor Bishop scores, achieving high rates of successful vaginal delivery.